EMPOWERMENT OF POOR COMMUNITIES THROUGH THE FAMILY HOPE PROGRAM (PKH) IN TELUK AMBON DISTRICT, AMBON CITY - Yusnizar Sitorus; Zainal Abidin Rengifurwarin; Ivonny Yeany Rahanra (Holistik Analisis Nexus, 2025)
The Family Hope Program (PKH) is a government initiative aimed at alleviating poverty through empowering poor communities in various regions. This study aims to analyze the implementation of PKH in Teluk Ambon District, focusing on program effectiveness, challenges faced, and the impact on beneficiaries. The research uses a qualitative case study approach, collecting data through interviews, observations, and documentation. The findings reveal that PKH implementation generally runs according to schedule and targets the right beneficiaries, despite some technical difficulties and challenges in data updating and public understanding. Coordination among stakeholders, continuous socialization, and optimal assistance are key factors for the program’s success. Moreover, PKH has significantly improved the welfare of poor families, especially in education and health sectors. However, improvements in monitoring and evaluation mechanisms and program flexibility are needed to better respond to social changes. This study recommends enhancing administrative systems and increasing the capacity of facilitators to ensure that PKH can be more effective and sustainable.